2021
DOI: 10.1002/mus.27349
|View full text |Cite
|
Sign up to set email alerts
|

A patient‐focused survey to assess the effects of the COVID‐19 pandemic and social guidelines on people with muscular dystrophy

Abstract: Introduction/Aims In this study, we examined the social and health impacts of the coronavirus disease 2019 (COVID‐19) pandemic and social guidelines on people with muscular dystrophies. Methods A prospective de‐identified electronic survey was distributed to adults with self‐reported facioscapulohumeral muscular dystrophy (FSHD), myotonic dystrophy (DM), and limb‐girdle muscular dystrophy (LGMD) enrolled in national registries or with patient advocacy groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
3
9
1
Order By: Relevance
“…However, this may be due to the small numbers in our sample as only 6.7% reported being non-Caucasian and 4.7% reported as Hispanic/Latino. The social strategies employed to reduce the spread of COVID-19, challenges due to the pandemic and social distancing, and research participation reported by participants at the second time point were similar to our findings at the beginning of the pandemic [4].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…However, this may be due to the small numbers in our sample as only 6.7% reported being non-Caucasian and 4.7% reported as Hispanic/Latino. The social strategies employed to reduce the spread of COVID-19, challenges due to the pandemic and social distancing, and research participation reported by participants at the second time point were similar to our findings at the beginning of the pandemic [4].…”
Section: Discussionsupporting
confidence: 85%
“…We found that participants reported challenges with obtaining treatment and essentials, stress management, and social distancing. They also reported moderate stress levels, which were comparable to the general population [4].…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations